A Self-paced Tutoring System, ILSA: Which System Utilization aligned with Learners' Goal Orientations? - Tecson, Cesar A (Archīum Ateneo, 2021)
For several decades, the role of computers has been appreciated in achieving various educational goals. Computer-assisted instructions become very popular in educational settings nowadays. Various intelligent tutoring systems have been developed to support learning in different contexts. This work investigates a tutoring system for learning Finite State Machines (FSM), one of the models of computation in Automata Theory, called ILSA. ILSA was deliberately developed to appeal to learners' achievement goal orientations. Achievement Goal Orientation theory suggests that learners could be mastery-oriented or performance-oriented. Hence, the specific aim of this investigation is to examine if there is evidence of alignment between system utilization and achievement goal orientations of learners. In other words, did the learners use the features of ILSA according to their respective orientation? Results showed that the goal orientations in Post-ILSA 1 have high manifestations of alignment between utilization and achievement goal orientations.